The mechanical properties, microstructures and mechanism of carbon nanotube-reinforced oil well cement-based nanocomposites. Issue 46 (27th August 2019) - Lu, Shichao; Wang, Xiaoyan; Meng, Zhaorui; Deng, Qingchun; Peng, Fangfang; Yu, Chengcheng; Hu, Xu; Zhao, Yi; Ke, Yangchuan; Qi, Fengzhong
Abstract : The reinforcing and toughening mechanism of MWCNTs in cementitious nanocomposites under the external load. Abstract : High performance cement-based nanocomposites were successfully fabricated through the use of oil well cement filled with multiwalled carbon nanotubes (MWCNTs) as reinforcements. The dispersibilities of four dispersing agents for the MWCNTs were investigated and compared. The dispersed morphologies and structural characteristics of the MWCNTs were analyzed via TEM, FTIR and Raman spectroscopy studies. The effects of MWCNT addition on the rheological behavior and fluidity of oil well cement slurry were discussed. The mechanical properties of the cement-based nanocomposites with different MWCNT content values and different curing ages were explored and analyzed. Furthermore, the microstructures of the MWCNT reinforced cementitious nanocomposites were characterized via XRD, SEM, EDS, total porosity and pore size distribution studies. The results demonstrated that the 28 day compressive strength and 28 day flexural strength of the 0.05 wt% MWCNT cementitious nanocomposite increased by 37.50% and 45.79%, respectively, compared with a pure cement matrix. The elastic moduli of a 0.05 wt% MWCNT cementitious sample declined by 19.07% and 35.39% under uniaxial and triaxial stress, respectively. XRD and pore structure analysis indicated that the MWCNTs could accelerate the hydration process, increase the amount of hydration products and optimize the pore size distribution within the matrix. Additionally, crack bridging, pulling out, network filling and a calcium-silicate-hydrate (C–S–H) phase were exhibited by SEM images. Meanwhile, the reinforcing and toughening mechanism of MWCNTs was also discussed; these had a beneficial influence on the mechanical properties.